Comparison of semiquantitative and differential time to positivity methods for the diagnosis of central line-associated bloodstream infections in an intensive care unit. Issue 4 (5th June 2019) - Karampatakis, Theodoros; Tsergouli, Katerina; Karantani, Ekaterini; Diamantopoulou, Anna; Mouloudi, Eleni; Roilides, Emmanuel; Karyoti, Angeliki
Abstract : Introduction. Central line-associated bloodstream infections (CLABSIs) adversely affect patients' hospitalization. Aim. We compared semiquantitative roll plate (SQRP) and differential time to positivity (DTP) culture methods in diagnosing CLABSIs. Methodology. A retrospective study was conducted in an intensive care unit (ICU) from January 2013 to August 2014. All ICU patients with suspected CLABSIs were included. Blood cultures were taken, while central venous catheter (CVC) tips were cultured using the roll-tip method. DTP was considered positive if CVC lumen blood cultures became positive at least 2 h prior to concurrently drawn peripheral blood cultures with an identical micro-organism. SQRP method was considered positive when ≥15 c.f.u. of a micro-organism identical to that of blood cultures grew. Measures of diagnostic accuracy were calculated. Results. SQRP displayed high sensitivity (94.7 %), while DTP showed high specificity (82.5 %). SQRP combined with DTP displayed 100  % sensitivity and negative predictive value. Conclusion. SQRP and DTP methods should be evaluated in combination.